IDENTIFIKASI RHODAMIN B PADA LIPSTIK YANG BEREDAR DI KOTA BENGKULU DENGAN METODE SPEKTROFOTOMETRI UV-VISIBEL - Rahmawati, Suci; Retnowati, Dwi; Hermansyah, Oky; Slamet, Samwilson (Poltekkes Kemenkes Bengkulu, 2024)
The use of the dye rhodamine B as a color additive in cosmetics has been prohibited by the Regulation of the Head of the Food and Drug Monitoring Agency (BPOM) Number: HK.00.05.42.1018 concerning Additional Ingredients in Cosmetics, because rhodamine B has carcinogenic properties if used long term in the body. In this research, 10 lipstick samples were used purposively obtained from the market in Bengkulu City. Lipstick samples were selected based on the criteria that they did not meet BPOM distribution requirements. Determination of rhodamine B levels was carried out using the UV-Visible Spectrophotometry method. The maximum wavelength used in the identification of Rhodamine B is 554 nm. The test results of ten lipsticks showed that nine lipsticks contained rhodamine B, in lipsticks with codes L2, L3, L4, L5, L6, L7, L8, L9 and L10 with a percentage of 0.0058%-0.0242%, and only one sample that was identified negative, L1 with an absorbance value of 0.364 with a percentage of 0%. In this study it can be concluded that there were 9 samples of 10 lipstick samples that were identified as containing Rhodamine B quantitatively.